“An Unspeakable Crime”: Divisions in Halifax Press Opinion Toward the July Crisis and Outbreak of the First World War - Caswell, Liam (Journal of the Royal Nova Scotia Historical Society, 2025)
More than a century after the outbreak of the First World War, the perception of a monolithically enthusiastic public response to the war’s commencement has endured in the popular imagination. While scholars have produced a large corpus of works dissecting and refuting the myth of unchallenged war enthusiasm among European populations during the summer of 1914, there have been relatively few comparable challenges to the narrative in a Canadian context. By comparing the attitudes expressed by Halifax’s two most widely circulated daily newspapers—the Liberal-leaning Morning Chronicle and the Conservative-affiliated Halifax Morning Herald—between the assassination of Archduke Franz Ferdinand and the British Empire’s first bloodletting at Mons, this article explores how initially divisive the popular press reaction was toward the possibility, and eventual reality, of Halifax’s participation in a major European War. Considering these divisions within the Halifax press as symptomatic of wider popular dissention of opinion, it is demonstrated how the Maritimes’ largest urban population was far from unanimous in their reaction to the July Crisis and the outbreak of the First World War.